2021
DOI: 10.1186/s12882-021-02428-5
|View full text |Cite
|
Sign up to set email alerts
|

The potential renal toxicity of silver nanoparticles after repeated oral exposure and its underlying mechanisms

Abstract: Background Silver nanoparticles (AgNPs) can accumulate in various organs after oral exposure. The main objective of the current study is to evaluate the renal toxicity induced by AgNPs after repeated oral exposure and to determine the relevant molecular mechanisms. Methods In this study, 40 male Wistar rats were treated with solutions containing 30, 125, 300, and 700 mg/kg of AgNPs. After 28 days of exposure, histopathological changes were assessed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 41 publications
2
18
2
Order By: Relevance
“…ROS may interact with macromolecules inside the cells, severely harming biological components [ 51 ]. In line with our findings, other investigations have demonstrated that AgNPs generate oxidative stress in kidney tissues [ 41 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…ROS may interact with macromolecules inside the cells, severely harming biological components [ 51 ]. In line with our findings, other investigations have demonstrated that AgNPs generate oxidative stress in kidney tissues [ 41 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…The animals treated with AgNPs suffered from nephrotoxicity and experienced a severe renal failure [ 43 ]. These results may be explained by the possibility that AgNP-induced oxidative stress promotes the generation of many vasoactive mediators, which can impair the renal function by causing renal vasoconstriction or by lowering the glomerular capillary ultra-filtration coefficient, which consequently decreases the glomerular filtration rate [ 44 ]. Note that an oral administration of Eug to AgNP-treated rats restored the serum levels of BUN, creatinine, and uric acid, suggesting that Eug offers a defense against AgNP-induced nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, intra-arterial injection of nanoparticles carries risks of increased nanoparticle binding to blood components and can potentially lead to thrombi or stenosis. Moreover, during the therapy, circulating nanoparticles may interact with the kidneys [49,50], leading to a worst-case renal tubule blockage. Accordingly, a prerequisite for the preparation of nanoparticles will be the maximum delineation of nanoparticle sizes that are safe for administration to animals and, subsequently, to humans.…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena were demonstrated in various human cell lines (keratinocytes, [147], hepatic, neuronal, lung epithelial, and murine stem cells), as well as animal tissues and organs [147]. Repeated exposure to AgNPs can potentiate inflammatory responses, activate the innate immunity [148], and have been associated with renal- [149], hepatic-and genotoxicity [147]. Even at non-cytotoxic doses, repeated doses of AgNPs may be detrimental to vital organs, resulting in their dysfunction and possibly total organ failure [150].…”
Section: Toxicity Of Agnpsmentioning
confidence: 99%